Management of obsessive compulsive disorder induced by the use of clozapine - Yunus Emre Donmez (Medicine Science, 2019)
The second generation antipsychotic of clozapine has superior efficacy compared to other antipsychotics especially for treatment-resistant schizophrenia. In up to 20% of patients receiving clozapine treatment, the side effect of obsessive compulsive symptoms or obsessive compulsive disorder occurs. These obsessive compulsive side effects sometimes cause cessation of the use of clozapine and sometimes causes difficulties in treating the psychotic symptoms due to dose reductions. This manuscript presents a case with resistant schizophrenia who developed obsessive compulsive disorder secondary to clozapine treatment and was successfully treated with clomipramine and aims to discuss the case accompanied by the literature. [Med-Science 2019; 8(2.000): 449-50]